2018
DOI: 10.7554/elife.38278
|View full text |Cite
|
Sign up to set email alerts
|

The lost world of Cuatro Ciénegas Basin, a relictual bacterial niche in a desert oasis

Abstract: Barriers to microbial migrations can lead adaptive radiations and increased endemism. We propose that extreme unbalanced nutrient stoichiometry of essential nutrients can be a barrier to microbial immigration over geological timescales. At the oasis in the Cuatro Ciénegas Basin in Mexico, nutrient stoichiometric proportions are skewed given the low phosphorus availability in the ecosystem. We show that this endangered oasis can be a model for a lost world. The ancient niche of extreme unbalanced nutrient stoic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…P. aeruginosa is a very well‐studied species, but in order to explore the possibility of isolating new P. aeruginosa lineages and to understand the origin of its pathogenic potential, we have characterized isolates from diverse environments (Grosso‐Becerra et al ., ). In this work, we explore the Cuatro Ciénegas Basin (CCB) located in the Chihuahuan Desert in the Mexican State of Coahuila, a place previously referred as a lost world due to the presence of ancient bacterial lineages (Souza et al ., ). We have observed that in CCB microbial diversity is extremely high (Souza et al ., ) and a large portion of it seems to include direct descendants of marine organisms (Souza et al ., ; Alcaraz et al ., ) including marine virus (Desnues et al ., ; Taboada et al ., ), which is atypical for lagoons and springs outside CCB.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…P. aeruginosa is a very well‐studied species, but in order to explore the possibility of isolating new P. aeruginosa lineages and to understand the origin of its pathogenic potential, we have characterized isolates from diverse environments (Grosso‐Becerra et al ., ). In this work, we explore the Cuatro Ciénegas Basin (CCB) located in the Chihuahuan Desert in the Mexican State of Coahuila, a place previously referred as a lost world due to the presence of ancient bacterial lineages (Souza et al ., ). We have observed that in CCB microbial diversity is extremely high (Souza et al ., ) and a large portion of it seems to include direct descendants of marine organisms (Souza et al ., ; Alcaraz et al ., ) including marine virus (Desnues et al ., ; Taboada et al ., ), which is atypical for lagoons and springs outside CCB.…”
Section: Introductionmentioning
confidence: 97%
“…In this work, we explore the Cuatro Ciénegas Basin (CCB) located in the Chihuahuan Desert in the Mexican State of Coahuila, a place previously referred as a lost world due to the presence of ancient bacterial lineages (Souza et al ., ). We have observed that in CCB microbial diversity is extremely high (Souza et al ., ) and a large portion of it seems to include direct descendants of marine organisms (Souza et al ., ; Alcaraz et al ., ) including marine virus (Desnues et al ., ; Taboada et al ., ), which is atypical for lagoons and springs outside CCB. We think that this is given in part by the ion composition of its water that is rich in sulphur and magnesium salts and poor in phosphorous and iron.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations